(untitled) (Research, Society and Development, 2021)
This paper aims to analyze the industrial profile of The State of Rio Grande do Sul, seeking to answer the following question: Is it occurring a process of deindustrialization in The State of Rio Grande do Sul? In this sense, were adjusted two Vector Error Correction Models (VEC), with the following dependent variables: exports of manufacturing industry (high intensity, medium-high, medium-low and low intensity) of The State of Rio Grande do Sul and exports of non-industrial products. The independent variables were real effective exchange rate; price index of non-energy commodities; and coefficient of the commercial openness degree. The results indicated that the exports of non-industrial products presented a greater increase than the products by technological intensity. In relation to the estimation of VEC, the results indicated that the exchange devaluation stimulates the exports; the commercial openness was extremely damaging to the exports and the price index of non-energy commodities variable presented opposite sign to the expected. Finally, we concluded that there are strong evidences of the deindustrialization process in The State of Rio Grande do Sul.